Integration of slingram (geonics em34-3) and Schlumberger configuration for groundwater exploration and development of Ayegunle-Oka, southwestern Nigeria - Okpoli, Cyril C; Oni, Olanrewaju P (International Journal of Advanced Geosciences, 2024)
The exploration and development of groundwater in the Precambrian Basement Complex of Ayegunle / Oka Akoko was necessitated because of perennial scarcity of potable water for communal purposes. The study was aimed at delineating the prolific aquiferous zones by the use of electromagnetic and Schlumberger- Vertical Electrical Sounding (VES) methods. Twenty (20) electromagnetic (EM) and electrical resistivity traverses of 100m long were carried out using Geonics co-planar loop system and ABEM SAS1000 Terameter. The EM and VES data were plotted against station position inverted and analyzed in terms of the conductivity and geo-electric parameter (apparent resistivity, depth and thickness) distribution in the area. The EM and VES dataset was processed using Karous-Hjelt and WinResist softwares. The interpretation of the electromagnetic profiles revealed some conductive zones that were prioritized for depth sounding. The result showed crossover point that diagnostic of conductivity. The apparent resistivity, depth and thickness of the subsurface strata ranges from: 81-1299 Ωm, 0.5-105.1m and 0.5-76.9m respectively. The lithologic strata vary from topsoil, clay/sandy clay, weathered/partially weathered, fractured/basement bedrock. The hydro-geologic cross-sections were categorized into: high, midrange, and low groundwater potential. The geophysical survey data revealed that the study region has the potential to play a key role in delivering adequate drinkable water for rural residents.